2019
DOI: 10.1371/journal.pone.0222537
|View full text |Cite
|
Sign up to set email alerts
|

Excellent outcome after desensitization in high immunologic risk kidney transplantation

Abstract: IntroductionHLA-incompatible (HLAi) and ABO-incompatible (ABOi) kidney transplantation (KT) has been on the increase over the last decade. However, there are wide variations in outcomes from these procedures. In this study we evaluated the graft and patient outcomes in incompatible KT and non-sensitized KT.MethodsPatients who underwent KT between January 2012 and April 2018 were enrolled and reviewed. We divided kidney transplant recipients (KTRs) into five groups as follows: HLAi (n = 50); ABOi (n = 65); HLAi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
4
21
2
Order By: Relevance
“…Therefore, the 5-year overall PS (98%) and GS (92%) rates in this study showed much better outcomes than those in European and United Network for Organ Sharing data [ 39 , 40 ]. However, recent studies involving Asian or Korean patients have reported similar clinical outcomes as those in our study [ 41 , 42 ]. Consideration of these factors are needed to interpret the results.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the 5-year overall PS (98%) and GS (92%) rates in this study showed much better outcomes than those in European and United Network for Organ Sharing data [ 39 , 40 ]. However, recent studies involving Asian or Korean patients have reported similar clinical outcomes as those in our study [ 41 , 42 ]. Consideration of these factors are needed to interpret the results.…”
Section: Discussionsupporting
confidence: 87%
“…The present study compares the characteristics of different kinds of living donor, incompatible kidney transplants. Published studies report that the proportion of female patients is higher in the HLAi group due to sensitization from pregnancy 14,15,22‐26 . This was different from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, a statistically significant difference was found in number of sensitizing events; blood transfusions, pregnancies and previous transplant between HLAc and HLAi recipients. This was similar to the study conducted by Lim et al 25 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations